Faktor-faktor Yang Mempengaruhi Program Asuransi Usaha Ternak Sapi (AUTS) Di Kulon Progo - Tri Kurniaty (Politeknik Kampar, 2024)
Livestock businesses have various risk of death including accidents, natural disasters including disease outbreaks, in this regard, then in accordance with Law Number 19 of 2013 concerning Protection and Empowerment of Farmers and Regulation of the Minister of Agriculture Number 40 / Permentan / SR.230 / 7/2015 regarding Agricultural Facilitation Insurance, agricultural insurance is required. The Ministry of Agriculture of the Republic of Indonesia implements agricultural insurance specifically aimed at the livestock business sector, this is a form of the government's part of it in protecting farmers from the risk of death and / or loss of livestock. cattle business insurance, as well as being able to provide education to breeders in managing risks and a good livestock business system. . This study aims to describe the implementation of cattle business insurance and determine what are the influencing factors in running cattle business insurance. The location selection was carried out by purposive sampling based on insurance program data. Primary data were obtained from 53 farmers with the help of a questionnaire. The basic method used in this research is descriptive method. Factors that influence the insurance program in Kulon Progo district are conditions and adjustment factors. Condition factors consist of extension variables and uncertainty, while adjustment factors consist of uncertainty, environmental risk, and market equilibrium variables.